2013
DOI: 10.1016/s1003-6326(13)62826-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution of copper–titanium alloy during in-situ formation of TiB2 particles

Abstract: Bulk Cu-Ti alloy reinforced by TiB 2 nano particles was prepared using in-situ reaction between Cu-3.4wt.% Ti and Cu-0.7wt.% B along with rapid solidification and subsequent heat treatment for 1-10 hrs at 900ºC. High-resolution transmission electron microscopy (HRTEM) characterization showed that primary TiB 2 nano particles and TiB whiskers were formed by in-situ reaction between Ti and B in the liquid copper. Formation of TiB whiskers within the melt led to coarsening of TiB 2 particles. Primary TiB 2 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This is believed was a side effect of limiting 211 the amount of liquid phase during the sintering process. A comparison of a grain size presented in Figure 8 shows that the introduction of titanium of particle size of 63 µm (Figure 8a) results in grain refinement, which stays in good agreement with other researchers' findings [26][27][28]. A similar trend was observed when titanium was introduced in the form of bigger particles (140 µm).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This is believed was a side effect of limiting 211 the amount of liquid phase during the sintering process. A comparison of a grain size presented in Figure 8 shows that the introduction of titanium of particle size of 63 µm (Figure 8a) results in grain refinement, which stays in good agreement with other researchers' findings [26][27][28]. A similar trend was observed when titanium was introduced in the form of bigger particles (140 µm).…”
supporting
confidence: 89%
“…Contrary to the REF sample, the more 207 titanium was introduced, the more developed the grains' shapes became. The presence of the TiB2 in 208 the matrix of the material may effectively hinder the grain growth, as was demonstrated in research 209 carried out, e.g., by Namini et al, Sobhani et al and Gan et al [26][27][28]. Moreover, the more titanium 210 was added, the more and the larger pores were observed.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[1] Studies have shown that the TiB 2 particles (TiB 2p ) and TiB whiskers (TiB w ) are two promising ceramic phases with low resistivity, high hardness, high modulus, and good chemical stability. [2] However, the agglomeration of reinforcements (TiB 2p and TiB w ) is easy to occur in the matrix when the composites are prepared by the traditional casting methods. [3] Many preparation methods, such as stirring casting, [4,5] rapid solidification, [6,7] and mixed casting, [8,9] have been proposed to improve the size, morphology, and distribution of reinforcements to obtain higher performances.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The hardness and bending strength of a copper matrix were both improved by adding a small amount of whiskers. 11,12 The strength of aluminum alloy or titanium alloy was also reinforced by addition or in situ growth of whiskers. 13,14 Such whiskers, which have diameters ranging from 0.2 lm to 2 lm and lengths less than 100 lm, are easily dispersed in composites.…”
Section: Introductionmentioning
confidence: 99%